Antimicrobial Potential of Secalonic Acids from Arctic-Derived Penicillium chrysogenum INA 01369 - Yulia A. Roshka; Natalia N. Markelova; Sofia D. Mashkova; Kseniya V. Malysheva; Marina L. Georgieva; Igor B. Levshin; Vladimir I. Polshakov; Alexander M. Arutyunian; Alexey S. Vasilchenko; Vera S. Sadykova (Antibiotics)
In this study, two compounds have been isolated from the Arctic-derived fungus Penicillium chrysogenum INA 13460. Structural elucidation, performed using 2D NMR and HR-ESIMS data, has identified the compounds as stereoisomers of secalonic acids, dimeric tetrahydroxanthones. The absolute configurations of these stereoisomers have been determined through conformational NMR analysis and circular dichroism spectroscopy. The antimicrobial activity of secalonic acids D and F has been evaluated against a diverse range of microorganisms, including Gram-positive multidrug-resistant Staphylococcus aureus, Gram-negative Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853, the phytopathogen Pectobacterium carotovorum VKM-B1247, and the fungi Fusarium oxysporum VKPM F 890, Aspergillus fumigatus VKM F-37, and A. niger ATCC 16404. Genomic and chemical analyses further support P. chrysogenum INA 13460 as a promising natural source for antimicrobial drug discovery and biological control applications.